"Do We Need to Know That for the Exam?" Teaching English on the CLIL Fault Line at a Trilingual University. Issue 2 (June 2015) - Ennis, Michael Joseph
<x xml:space="preserve">Abstract</x> This article describes how a course based on the concept of English for specific academic purposes (ESAP) was transformed into content and language integrated learning (CLIL) at a trilingual university where English serves as a lingua franca and medium of instruction, due to the application of a task‐based communicative approach. The article describes how the trilingual learning context (German, Italian, English), the specific needs of the students, the teaching methodology, the course design, and the assessment procedure unintentionally resulted in CLIL. These observations may suggest that all task‐based communicative language learning based on the input‐interaction‐output model of second language acquisition has the potential to transform into CLIL when applied to a specific academic context, especially one in which the target language serves as a medium of instruction. But a more detailed and systematic study is required to determine the effectiveness of this particular CLIL course within this unique learning environment.